Ion kinetics in a hot flow anomaly: MMS observations - Schwartz,SJ; Avanov,L; Turner,D; Zhang,H; Gingell,I; Eastwood,JP; Gershman,DJ; Johlander,A; Russell,CT; Burch,JL; Dorelli,JC; Eriksson,S; et al. (Geophysical Research Letters, 2018)
Hot Flow Anomalies (HFAs) are transients observed at planetary bow shocks, formed by the shock interaction with a convected interplanetary current sheet. The primary interpretation relies on reflected ions channeled upstream along the current sheet. The short duration of HFAs has made direct observations of this process difficult. We employ high resolution measurements by NASA's Magnetospheric Multiscale Mission to probe the ion microphysics within a HFA. Magnetospheric Multiscale Mission data reveal a smoothly varying internal density and pressure, which increase toward the trailing edge of the HFA, sweeping up particles trapped within the current sheet. We find remnants of reflected or other backstreaming ions traveling along the current sheet, but most of these are not fast enough to out-run the incident current sheet convection. Despite the high level of internal turbulence, incident and backstreaming ions appear to couple gyro-kinetically in a coherent manner.